On the Anomalously Strong Dependence of the Acoustic Velocity of Alumina on Temperature in Aluminosilicate Glass Optical Fibers—Part II: Acoustic Properties of Alumina and Silica Polymorphs, and Approximations of the Glassy State. (27th August 2015) - Ballato, Arthur; Dragic, Peter D.; Martin, Steve W.; Ballato, John
Abstract : The companion paper (Part I; Dragic et al ., this issue), 1 resolved an anomaly involving the acoustical properties of high alumina content glass optical fibers. In Part II, some attributes of alumina and silica polymorphs are considered and used to infer approximate pertinent properties of amorphous Al2 O3 "glass." An efficient computational method is used, based on a simple, self‐consistent version of the Voigt‐Reuss‐Hill procedure. Applied to SiO2 polymorphs, it provides insights into the short‐range ordering in "amorphous" silica.